2021
DOI: 10.1002/iid3.505
|View full text |Cite
|
Sign up to set email alerts
|

The study on the function and cell source of interleukin‐6 in interstitial cystitis/bladder painful syndrome rat model

Abstract: Objective The elevated expression of interleukin‐6 (IL‐6) in patients with interstitial cystitis/bladder painful syndrome (IC/BPS) has been demonstrated, but the role of IL‐6 in IC/BPS and its source remain to be explored. Methods IC/BPS rat model was created in female rats by using long‐term intermittent intravesical hyaluronidase (0.5 ml, 4 mg/ml). After modeling, IL‐6 stimulation group, and anti‐IL‐6R group were treated with recombinant rat IL‐6 and tocilizumab, respectively. Symptomatic changes were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Further, lower urine levels of IL-6 may re ect lower severity of symptoms. In a recent study, the FDAapproved drug tocilizumab that binds IL-6 was shown to reduce bladder in ammation in a rat model, supporting the potential repurposing of tocilizumab for IC/BPS (43). Such mechanistic clinical trials have the added bene t of shedding light on the mystery of how temporally brief urinary elevation of IL-6 is able to mediate chronic in ammation associated with IC/BPS (9,10,25,27).…”
Section: Discussionmentioning
confidence: 94%
“…Further, lower urine levels of IL-6 may re ect lower severity of symptoms. In a recent study, the FDAapproved drug tocilizumab that binds IL-6 was shown to reduce bladder in ammation in a rat model, supporting the potential repurposing of tocilizumab for IC/BPS (43). Such mechanistic clinical trials have the added bene t of shedding light on the mystery of how temporally brief urinary elevation of IL-6 is able to mediate chronic in ammation associated with IC/BPS (9,10,25,27).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, stimulating bladder epithelial cells with IL1β induces the expression and release of IL6. Thus, IL6 is produced in the bladder epithelial and stromal layers [ 7 ] and is thought to play a role in cystitis development [ 25 ]. Indeed, it has been reported that urinary IL6 levels are higher in patients with IC than in healthy individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%